2020
DOI: 10.1007/s00705-020-04652-0
|View full text |Cite
|
Sign up to set email alerts
|

Cell fusing agent virus (Flavivirus) infection in Aedes aegypti in Texas: seasonality, comparison by trap type, and individual viral loads

Abstract: South Texas has experienced local transmission of Zika virus and of other mosquito-borne viruses such as chikungunya virus and dengue virus in the last decades. Using a mosquito surveillance program in the Lower Rio Grande Valley (LRGV) and San Antonio, TX, from 2016 to 2018, we detected the presence of an insect-specific virus, cell fusing agent virus (CFAV), in the Aedes aegypti mosquito population. We tested 6,326 females and 1,249 males from the LRGV and 659 females from San Antonio for CFAV by RT-PCR usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…In one of these households, the animals were resampled two weeks later and respiratory and body fur samples were again positive ( Hamer et al 2021 ). Furthermore, in our recent study using sticky traps for indoor and outdoor collections, we detected viral RNA of an insect-specific virus in 30% (40 of 138) of Aedes aegypti mosquito pools ( Martin et al 2020 ). Most of these mosquitoes were dead when collected at 7 d intervals confirming the utility of a sticky trap for recovering viral RNA in insects using the same protocols and equipment as the current study.…”
Section: Discussionmentioning
confidence: 92%
“…In one of these households, the animals were resampled two weeks later and respiratory and body fur samples were again positive ( Hamer et al 2021 ). Furthermore, in our recent study using sticky traps for indoor and outdoor collections, we detected viral RNA of an insect-specific virus in 30% (40 of 138) of Aedes aegypti mosquito pools ( Martin et al 2020 ). Most of these mosquitoes were dead when collected at 7 d intervals confirming the utility of a sticky trap for recovering viral RNA in insects using the same protocols and equipment as the current study.…”
Section: Discussionmentioning
confidence: 92%
“…The first detection was from Ae. aegypti cell lines [7], and it was later detected in field-caught Aedes and Culex mosquitoes in different parts of the world [9,[34][35][36]. CFAV appears to be a frequent flavivirus in mosquito populations, and the fact that it was not detected previously in South Africa is mostly likely due to lack of studies on ISFVs as opposed to a lack of presence.…”
Section: Discussionmentioning
confidence: 99%
“…Although improvements for testing male pupae exuviae would be desirable, the sensitivity of 89% for female pupae exuviae provides the ability to assess prior infection in mosquitoes by testing pupae exuviae, which will be useful for future experiments. It is unknown why sensitivity differs between female and male pupae exuviae, but a previous study has shown that virus levels have a wider range and are lower titer, on average, in males (Martin et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A small number of studies have observed vertical transmission of ISFs in naturally or experimentally infected mosquito colonies (Peinado et al 2022; McClean et al 2021; Contreras-Gutierrez et al 2017; Bolling et al 2012; Saiyasombat et al 2011; Lutomiah et al 2007), including for cell fusing agent virus (CFAV), an ISF identified in several Aedes aegypti cell culture lines, and in field and laboratory colony mosquitoes (Baidaliuk et al 2020; Martin et al 2020; Bolling et al 2015; Stollar and Thomas, 1975). The observed vertical transmission rate was higher in naturally infected colonies of Ae.…”
Section: Introductionmentioning
confidence: 99%